2014
DOI: 10.1063/1.4898395
|View full text |Cite
|
Sign up to set email alerts
|

Strong and weak, unsteady reconfiguration and its impact on turbulence structure within plant canopies

Abstract: Numerical evaluation of tree canopy shape near noise barriers to improve downwind shielding J. Acoust. Soc. Am. 123, 648 (2008); 10.1121/1.2828052 This article is copyrighted as indicated in the article. Reuse of AIP content is subject to the terms at: http://scitation. Flexible terrestrial and aquatic plants bend in response to fluid motion and this reconfiguration mechanism reduces drag forces, which protects against uprooting or breaking under high winds and currents. The impact of reconfiguration on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 60 publications
5
20
0
Order By: Relevance
“…Fitting the power-law dependence C d = (|ũ|/A) B to the data yields A = 0.29 m s −1 and B = −0.74 (see appendix B). The Vogel number B is within the theoretical range −1 < B < −2/3 for one-dimensional linear elastic bending in the regime of weak-to-strong reconfiguration Pan et al 2014). This value (B = −0.74) is similar to the experimental value B = −0.71 reported by Harder et al (2004) for the giant reed Arundo donax under flow rates u 1.5 m s −1 .…”
Section: Model Descriptionsupporting
confidence: 79%
“…Fitting the power-law dependence C d = (|ũ|/A) B to the data yields A = 0.29 m s −1 and B = −0.74 (see appendix B). The Vogel number B is within the theoretical range −1 < B < −2/3 for one-dimensional linear elastic bending in the regime of weak-to-strong reconfiguration Pan et al 2014). This value (B = −0.74) is similar to the experimental value B = −0.71 reported by Harder et al (2004) for the giant reed Arundo donax under flow rates u 1.5 m s −1 .…”
Section: Model Descriptionsupporting
confidence: 79%
“…With regard to RS, Case i and Case ii have the same RMSE = 0.23, and both simulations produced sharp peaks in RS that were not consistent with the measured profile of RS. The RMSE value for skewness improved slightly with the introduction of velocity-dependent C D , as was also noted in Pan et al (2014b). Both simulations produced a peak in Sk (u) that was closer to the top of the canopy than the observed peak skewness.…”
Section: Validation With Rigid Canopy Measurementssupporting
confidence: 66%
“…Finally, Sk (u) > 0 and Sk (w) < 0 inside the canopy, showing the importance of sweeps (u' < 0, w' > 0) in the downward momentum flux. There was better agreement with observations in Case ii, with a velocity-depended C D , than Case i, with a constant C D , indicating that the introduction of a velocity-dependent drag coefficient improved the prediction of skewness within the canopy, similar to the results in Pan's corn canopy (Pan et al, 2014a;Pan, Follett, Chamecki, Nepf, 2014b). The root mean square error (RMSE) was calculated to provide a quantitative comparison between simulation and measured data (Table 2).…”
Section: Validation With Rigid Canopy Measurementsmentioning
confidence: 57%
“…Pan et al (2014a, b) reported that using an instantaneous drag coefficient that followed a power law of instantaneous velocity with an exponent between −2/3 and −1 significantly improved the prediction of velocity skewness and the prediction of the fraction of vertical momentum flux carried by strong events. As the power-law exponent became more negative, the peak in the skewness of the streamwise velocity component increased in magnitude and its location moved downwards, corresponding to greater magnitude and penetration of strong downward events within the canopy (Pan et al 2014b). Given the sensitivity of high-order turbulence statistics to the choice of the power-law exponent, an accurate model of the instantaneous drag coefficient is critical for LES models to reproduce the structure of turbulence as well as the transport of scalars within and above the plant canopy.…”
Section: Introductionmentioning
confidence: 99%
“…For terrestrial and aquatic canopies, this dependence is commonly observed to follow a power law of the local characteristic velocity scales with an exponent between zero and −4/3 (Vogel 1984;Gaylord et al 1994;Harder et al 2004;Albayrak et al 2012;Queck et al 2012;Pan et al 2014a). For natural canopies in which simple bending is observed (e.g., seagrasses and wheat), both measurement and theory suggest a power-law exponent between −2/3 and −1 (Pan et al 2014b).…”
Section: Introductionmentioning
confidence: 99%